Natural Light Therapy to Lower Agitation and Sleep Disturbance of Dementia Patients in Semarang - Mendrofa, Fery A.M.; Hani, Umi; Putri, Arista A.; Aeni, Milatul (International Journal of Psychosocial Rehabilitation, 2020)
Agitation is the mismatch of verbal, vocal, and motor activities that are not based on clear or confused needs. This disorder is a common and challenging symptom affecting dementia patients and impacting on sleep quality. This study aims to describe the effect of light therapy on agitation and sleep disturbance experienced by dementia patients in Semarang. The study used a quasi-experimental with one group design pre and posttest. The research samples were 83 respondents using a purposive sampling technique. The respondents received a daily routine of light therapy over a seven day period. Pre and posttest data were obtained from the Pittsburgh Agitation Scale to obtain agitation level and sleep pattern observation sheet to observe sleep disturbance. For the empirical investigation, 32 men and 51 women were recruited (mean age 67.35 years). Of these, 100% of respondents suffered a moderate level of agitation and 34.9% had sleep disturbance observed from sleep hours in a day. A Wilcoxon test was conducted to compare the agitation levels and sleep disturbance before and after light therapy. Findings showed that agitation level and sleep disturbance decreased with the light therapy (z = (-8.11), p